ICE CREAM INDUSTRY BID FOR VEGETABLE FAT SUBSTITUTE BASED ON SWEET POTATO LOCAL RESOURCE IN MARDI - salsabilla, shinta; Fadhly Siregar, Aflahun; Rusli, Rawaida; Hashim, Hasnisa; Pono, Zawiyah (Jurnal Agristan, 2025)
The objective of this study is to identify the ice cream industry’s supply of sweet potato based vegetable fat subsitute products at MARDI. The research employed qualitative techniques using the case study method on ice cream entrepreneurs at the Malaysia Agriculture,Horticulture, and Agritourism (MAHA) 2024 held at MAEPS Serdang, Malaysia. The findings showed that the developed fat substitutes need to be improved in terms of consistency, flavour, stability during storage, as well as the ability to create a texture similar to animal fat. Nevertheless, industry players remained positive towards the developed fat substitute innovations. Fulfilling consumer tastes and competitive pricing of fat substitute are among the key challenges for the fat substitute industry to continue to grow in the future.